Shifting the Lens: An Implementation Study of a Community-Based and Social Network Intervention to Gender-Based Violence - Kim, Mimi E. (Violence against women, 2021)
Responding to the call to “shift the lens” and expand gender-based violence remedies beyond individualized direct services and law enforcement remedies, anti-violence providers have struggled to redefine and redirect intervention approaches. This implementation study leverages the framework of implementation science to investigate an exploratory statewide initiative based on the Creative Interventions model and aimed to build organizational and regional capacity to implement community-based or social network interventions within provider organizations. Using data from nine organizations, this mixed-methods study identifies factors related to implementation of this innovative approach including organizational motivation, capacity, and perceived needs related to adoption and implementation.